Digital economy, technological progress, and carbon emissions in Chinese provinces - Shen, Yuyan; Wang, Guoliang; Wu, Xudong; Shen, Ce (Scientific reports, 2024)
The 2023 work report of the Chinese government underscores a pivotal transition towards a “dual-control” policy, prioritizing the management of carbon emissions. This study provides an in-depth analysis of the interplay between the digital economy, technological progress, and their impact on the total volume and intensity of carbon emissions across 30 Chinese provinces from 2013 to 2021. Our findings reveal that while the expansion of the digital economy and technological progress contribute to an increase in the total carbon emissions, they also markedly decrease carbon intensity, paving the way for sustainability. Additionally, the research uncovers the positive externalities of the digital economy on carbon emission intensity and the spillover effects of technological progress on both emissions and intensity. The integration of the digital economy in industrial restructuring and the uptake of green technologies are identified as instrumental in mitigating carbon emissions. These insights underscore the potential of policy strategies that leverage the digital economy and technological innovation to meet the “dual-control” policy objectives and foster sustainable development.